Protesi femoro-rotulea - Pilone, C.; Dettoni, F.; Bonasia, D.E.; Rosso, F.; Cottino, U.; Rossi, R. (Lo Scalpello - Journal, 2019)
PATELLO FEMORAL ARTHROPLASTY Patellofemoral osteoarthritis is a common cause of anterior knee pain. Some authors reported an incidence of 9% in population over 40 years, with a higher prevalence in females. Patellofemoral arthroplasty (PFA) is a good option for patients with isolated patellofemoral osteoarthritis, preserving tibio-femoral joints. First generation implants (in-lay design) have shown high failure rates at medium term follow-up. Second generation prostheses (on-lay design), with an anterior femoral cut based on total knee replacement, have allowed for improvement at medium and long term. A proper patient selection is mandatory for the success of this procedure. The ideal candidate has isolated patellofemoral osteoarthritis non responsive to conservative treatment and an age between 40 and 60 years. The main cause of PFA failure is progression of tibio-femoral arthritis. In this case, good results have been provided by the association of PFA and unicompartmental knee arthroplasty. Conversion of a PFA to total knee arthroplasty (TKA) does not add particular difficulties compared to primary TKA. More studies are required to confirm long-term results and the application of robotic technologies to PFA.